A Quantitative Justification to Dynamic Partial Replication of Web Contents through an Agent Architecture - Torres-Franco, Enrique; García, José Daniel; Sanjuán Martínez, Óscar; Joyanes Aguilar, Luis; González-Crespo, Rubén (International Journal of Interactive Multimedia and Artificial Intelligence, 2017)
The most usual solution to improve the performance of a Web server is based on building a distributed architecture, where the Web server is offered from a set of nodes. The most widely distributed architecture is based on Web clusters including a Web switch. The Web switch is responsible for deciding which site's node must attend which request. When deciding where elements are stored the classical solution was to fully replicate all contents in every server node. However, partial replication may require a fraction of storage while offering the same level of reliability. In this paper we report a solution based on dynamic partial replication where the number of replicas for each file and its management is handled by an agent architecture. We compare our solution with full replication and with static partial replication both in terms of storage capacity consumption and service time. Our results show that our proposed solution provides equivalent performance with a better use of disk storage capacity.
Keywords: distributed computing; computer network performance; network servers; cooperative systems; Emerging; IJIMAI